What is ‘good evidence’ for environmental decision making? Insights from professionals working at the science-policy interface - Elizabeth A. Nyboer; Andrew N. Kadykalo; Nathan Young; Vivian M. Nguyen; Trina Rytwinski; John-Francis Lane; Joseph R. Bennett; Nathan Harron; Susan M. Aitken; Graeme Auld; David Browne; Aerin L. Jacob; et al. (Environmental Science & Policy, 2025)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Extirpations from Parks: Scaling Conservation Planning to Fit the Problem - Kent Prior (Conservation Biology, 2010)

Directional gene flow patterns in disjunct populations of the black ratsnake (Pantheropis obsoletus) and the Blanding’s turtle (Emydoidea blandingii) - Briar J. Howes; Joseph W. Brown; H. Lisle Gibbs; Tom B. Herman; Stephen W. Mockford; Kent A. Prior; Patrick J. Weatherhead (Conservation Genetics, 2009)

Hybridization between mtDNA‐defined phylogeographic lineages of black ratsnakes ( Pantherophis sp.) - H. LISLE GIBBS; SARAH J. COREY; GABRIEL BLOUIN‐DEMERS; KENT A. PRIOR; PATRICK J. WEATHERHEAD (Molecular Ecology, 2006)
Phylogeographic analyses using mitochondrial DNA (mtDNA) have revealed many examples of apparently deep historical subdivisions (‘phylogroups’) within many vertebrates. It remains unclear whether these phylogroups represent independently evolving, adaptively differentiated lineages or groups that show little functional differentiation and, hence, will merge on contact. Here, we use mtDNA sequence data to evaluate the phylogeographic relationships between two of the northernmost populations of black ratsnakes ( Pantherophis obsoletus complex) in Ontario, Canada and previously analysed populations in the United States. We then use population‐level analyses to evaluate the level of adaptive divergence between previously established mtDNA phylogroups. Phylogenetic analyses show that southern Ontario snakes have mtDNA haplotypes that fall within the Central mtDNA phylogroup, as designated by Burbrink et al . (2000 ). In contrast, snakes in eastern Ontario carry either Central or Eastern‐specific haplotypes. Within the hybrid region, we found highly variable frequencies of mtDNA haplotypes among isolated sub‐populations, no association between variation in cytonuclear (mtDNA) and nuclear (microsatellite DNA) markers, no difference in survival or reproductive success among snakes with different mtDNA haplotypes, and no effect of mate similarity in mtDNA on female clutch size. These results argue that the Eastern and Central phylogroups have merged in this region, likely due to a lack of adaptive differentiation between individuals in each lineage. Hence, in these snakes, phylogeographic structure in mtDNA is more a reflection of historical isolation rather than adaptive divergence. The observed reticulation between lineages and lack of evidence for hybrid disgenesis also bears on the classification of these lineages as distinct species.

Genetic structure of populations of the threatened eastern massasauga rattlesnake, Sistrurus c. catenatus : evidence from microsatellite DNA markers - H. Lisle Gibbs; Kent A. Prior; Patrick J. Weatherhead; Glenn Johnson (Molecular Ecology, 1997)
Throughout its distribution in North America, the threatened eastern massasauga rattlesnake ( Sistrurus c. catenatus ) persists in a series of habitat‐isolated disjunct populations of varying size. Here, we use six microsatellite DNA loci to generate information on the degree of genetic differentiation between, and the levels of inbreeding within populations to understand how evolutionary processes operate in these populations and aid the development of conservation plans for this species. Samples were collected from 199 individuals from five populations in Ontario, New York and Ohio. Our results show that all sampled populations: (i) differ significantly in allele frequencies even though some populations are F IS values (mean overall F IS = 0.194) probably due to a combination of Wahlund effects resulting from fine‐scale genetic differentiation within populations and the presence of null alleles. Our results imply that massasauga populations may be genetically structured on an extremely fine scale even within continuous populations, possibly due to limited dispersal. Additional information is needed to determine if dispersal and mating behaviour within populations can account for this structure and whether the observed differentiation is due to random processes such as drift or to local adaptation. From a conservation perspective, our results imply that these massasauga populations should be managed as demographically independent units and that each has high conservation value in terms of containing unique genetic variation.

Turkey vultures foraging at experimental food patches: a test of information transfer at communal roosts - Kent A. Prior; Patrick J. Weatherhead (Behavioral Ecology and Sociobiology, 1991)